Caracterização da diversidade molecular de Nogueira-pecã (carya illinoinensis) baseada em marcadores moleculares - Nagel , Jordana Caroline (2022)
The pecan tree (Carya illinoinensis [Wangenh.] K. Koch) belongs to the Juglandaceae family, and has a predominant distribution in the temperate regions of the Northern Hemisphere. Interest in its fruits has shown exponential growth in Brazil and other countries, especially for its high nutritional value. In addition, it is an income option for family farmers, due to its potential for use in legal reserve areas, becoming a kind of economic and social interest, especially in southern Brazil. Due to the lack of genetic information, lack of pollination control, and lack of records of propagule collection in orchards, genetic materials in cultivation generally do not have a completely known origin. In this sense, molecular characterization from molecular markers can solve this problem, identifying and distinguishing cultivars, and simultaneously providing the basis for planning an eventual program for the genetic improvement of the species. In addition, it would also contribute to the improvement of the orchard management system, with direct repercussions on productivity. The present work aimed to sequence the plastid DNA of the Imperial cultivar, using it to develop microsatellite markers and later to evaluate, concomitantly with universal plastid microsatellite markers and species-specific nuclear microsatellite markers, the genetic diversity existing among the cultivars planted in Rio Grande do Sul. In the complete DNA sequencing (cpDNA) of C. illinoinensis cv Imperial, it was found that the genome is 160,818 base pairs (bp) long, with a quadripartite structure with LSC of 90,041 bp, SSC of 18,791 bp and two IRs of 25,993 bp . A total of 78 protein-coding regions, 37 tRNA-coding regions and eight rRNA-coding regions were predicted. For the prospection, characterization and validation of the first plastid microsatellite markers for the species, data obtained from the sequencing of the plastome C. illinoinensis cv Imperial were used. To validate the markers, genomic DNA was isolated from leaves collected from 14 cultivars and the 10 pairs of plastid primers prospected were amplified via PCR reaction and the alleles separated via agarose gel electrophoresis. The in silico transferability test of the markers resulted in amplification of 10 loci in C. illinoinensis cultivars, nine in species of the genus Carya and seven in the genus Juglans, suggesting its potential for application in genetic studies of these species. In the validation of markers in C. illinoinensis cultivars, only the cpCil1 locus did not amplify for the Choctaw cultivar, and there was no amplification for the cpCil8 and cpCil9 loci in the Chickasaw cultivar. For the analysis of the genetic divergence of the cultivars, 10 nuclear (SSR) and 13 plastid (cpSSR) microsatellite markers were tested. Through the analysis of principal coordinates (PCoA) of the nSSR, the two components explained, in total, 21.39% of the total variability observed, while for the cpSSR the total of 84.65%. Despite the high cophenetic correlation value (cpSSR= 0.9931 and nSSR= 0.9791), bootstrap values in the larger clusters were low. The results obtained in this study showed high genetic diversity for both nuclear (I= 2.365) and plastid (I= 2.183) markers. This estimate of genetic diversity is very significant, and this result can be used to determine the genetic pattern of the analyzed cultivars. This is the first study on the development and characterization of species-specific plastid microsatellite markers for C. illinoinensis with potential applicability to generate information about genetic diversity among cultivars of the species. The data obtained so far allow us to help in deepening the analysis of genetic diversity, because through recent studies, open pollination promotes high genetic segregation, and propagation through seeds may have introduced hundreds of pecan varieties around the world. This great diversity in the form of the fruits, the trees, the quality of the nuts and their different ways of reproducing, still causes a great confusion regarding the nomenclature and the identification